Comparison of Private Incentive Mechanisms for Improving Sustainability of Filipino Tuna Fisheries. (July 2016) - Tolentino-Zondervan, Frazen; Berentsen, Paul; Bush, Simon; Idemne, Joseph; Babaran, Ricardo; Lansink, Alfons Oude
Highlights: We analyzed and compared different private incentive mechanisms for improving sustainability in Philippine tuna fishery. Availability of capabilities is a condition for upgrading in tuna global value chain. Upgrading is required to realize the incentives of private incentive mechanisms. The incentives delivered by private incentive mechanisms must offset the additional risks and costs of upgrading. Support of capability development of fishers should be part of a successful incentive mechanism. Summary: This paper analyzes the influence of three private incentive mechanisms over decision making related to improved sustainability of fishing practices in Filipino tuna fisheries. The three mechanisms compared are the World Wildlife Fund for Nature's fishery improvement project model, Marine Stewardship Council certification, and the International Seafood Sustainability Foundation Pro-Active Vessel Register. The main question addressed in this paper is how and to what extent the private incentive mechanisms support the development of fisher capabilities to respond to the requirements set out by these mechanisms. Applying a global value chain approach to analyze results collected from key actors involved in Philippine tuna fishers contributing to both domestic and regional economic development in the Western Pacific, we explore the structure and function of these private incentive mechanisms in achieving both environmental and economic development outcomes. Our results show that these private incentive mechanisms deliver different direct and indirect incentives for changing to more sustainable fishing practices, and that the success of these mechanisms is dependent on the extent to which the mechanisms support the development of target fisher capabilities to comply with their sustainability requirements. We conclude that the future success of these incentive mechanisms depends for a large part on stricter sustainability requirements, but also on the capacity of the mechanisms to incentivize the inclusion of more developing country fishers. These findings contribute to a wider understanding of how the capabilities of developing country producers are influenced by their relationship with chain and non-chain actors, and with the wide institutional arrangements that the producers operate in.